Analisis Kemampuan Pemecahan Masalah Matematika Siswa Melalui Soal Kelas II SDN 1 Selabintana - Novi Nuraulia; Din Azwar Uswatun; Andi Nurrochmah (JIKAP PGSD: Jurnal Ilmiah Ilmu Kependidikan, 2020)
This study aims to describe the students' mathematical problem solving abilities and the factors that influence the mathematical problem solving abilities of students in grade II of SDN 1 Selabintana. This type of research uses qualitative methods with a descriptive approach. Data collection techniques in this study were through observation and in-depth interviews. The data source of this research was in the form of data from interviews with grade II teachers of SDN 1 Selabintana. The data analysis technique uses the Miles and Huberman analysis model which is done interactively and continuously until it is complete so that the data is saturated. The results of this study indicate that the ability to solve mathematical problems through Class II questions SDN 1 Selabintana include: Ability to understand questions, ability to plan problem solving, the ability to answer and solve problems, and the ability to check the results of answers. As well as the factors that influence the mathematical problem solving ability of students in grade II SDN 1 Selabintana include: Learning difficulties, concentration, motivation, critical thinking skills, learning enthusiasm, learning media, and professional educators.